Development of Blood-Brain Barrier Permeable Nanoparticles as Potential Carriers for Salvianolic Acid B to CNS - Grossi, Cristina; Guccione, Clizia; Isacchi, Benedetta; Bergonzi, Maria Camilla; Luccarini, Ilaria; Casamenti, Fiorella; Bilia, Anna Rita (Planta Medica, 2017)
The blood-brain barrier hinders the passage of systemically delivered therapeutics and the brain extracellular matrix limits the distribution and durability of locally delivered agents. Drug-loaded nanocarriers represent a promising strategy to overcome these barriers and address specific drug delivery challenges due to their small size and versatile design. We synthetized [fluorescent poly(ethyl-cyanoacrylate) nanoparticles coated with Tween 80 by an emulsion polymerization method to target and reach the brain after intravenous and intraperitoneal administration. Nanoparticles were characterized in terms of dimensional analysis, polydispersity and zeta potential (ζ-potential), morphology, encapsulation efficacy, and loading capacity. After intracerebral injection in healthy rats, nanoparticles were distributed within the injected hemisphere and mainly interacted with microglial cells, presumably involved in their clearance by phagocytosis. Furthermore, nanoparticles were able to pass the blood-brain barrier after systemic administration in rats, and the lack of toxicity in C57/B6 mice chronically administered was highlighted. The data obtained helped to clarify the nanoparticles distribution, accumulation, fate, and toxicity into the brain. The selected nanoparticles may represent a biocompatible promising carrier to be further investigated as brain delivery systems. Salvianolic acid B from Salvia miltiorrhiza is a promising molecule in the protection of degeneration in several animal models by various biological mechanisms, but its poor chemical stability and low bioavailability limits its clinical application for central nervous system neuronal injury and degeneration. Nanoparticles were loaded with salvianolic acid B obtaining an encapsulation efficacy and loading capacities of 98.70 % ± 0.45 and 53.3 % ± 0.24, respectively. They were suitable for parental administration because their mean diameter was smaller than 300 nm, with a polydispersity of 0.04 ± 0.03, and a ζ-potential of − 8.38 mV ± 3.87. The in vitro release of salvianolic acid B from the nanoparticles was sustained and prolonged during 8 h, suitable for a promising clinical application.
Keywords: poly(ethyl cyanoacrylate) nanoparticles; blood-brain barrier; in vivo studies; behavioral test; biocompatibility; salvianolic acid B